The Added Benefit of Opicapone When Used Early in Parkinson's Disease Patients With Levodopa-Induced Motor Fluctuations: A Post-hoc Analysis of BIPARK-I and -II - Rocha, José-Francisco; Ebersbach, Georg; Lees, Andrew; Tolosa, Eduardo; Ferreira, Joaquim J.; Poewe, Werner; Rascol, Olivier; Stocchi, Fabrizio; Antonini, Angelo; Magalhães, Diogo; Gama, Helena; Soares-da-Silva, Patrício (Frontiers in Neurology, 2021)
Introduction: Opicapone (OPC) was efficacious in reducing OFF-time in two pivotal trials in patients with Parkinson’s disease (PD) and end-of-dose motor fluctuations (BIPARK-I and II). Post-hoc analyses of these trials evaluated the efficacy of OPC following pre-defined segmentation of the wide spectrum of motor fluctuations in PD. Methods: Data from matching treatment arms in BIPARK-I and II were combined for the placebo (PLC) and OPC 50 mg groups and exploratory post-hoc analyses were performed to investigate the efficacy of OPC 50 mg versus PLC in subgroups of patients who were in ‘earlier’ versus ‘later’ stages of both their disease course (e.g. duration of PD <6 years vs. ≥6 years) and levodopa treatment pathway (e.g. number of daily levodopa intakes <4 vs. ≥4). Efficacy variables included changes from baseline in absolute OFF-time and total ON-time. Results: The Full Analysis Set included 517 patients (PLC, n=255; OPC 50 mg, n=262). OPC 50 mg was significantly more effective than PLC in reducing OFF-time and increasing ON-time in the majority of subgroup analyses (p<0.05). Moreover, patients in ‘earlier’ stages of both their disease course and levodopa treatment pathway experienced numerically greater efficacy when using OPC 50 mg, in comparison with those in ‘later’ stages. Conclusion: OPC 50 mg was efficacious over the whole trajectory of motor fluctuation evolution in PD patients. There was also a signal for enhanced efficacy in patients who were earlier versus later in their disease course and levodopa treatment pathway.